2011
DOI: 10.1590/s0103-50532011000500002
|View full text |Cite
|
Sign up to set email alerts
|

A multicommuted flow system for dissolution studies of Captopril in pharmaceutical preparations

Abstract: Um procedimento analítico em sistema de análises em fluxo com multicomutação é proposto para a determinação de captopril e construção de curvas de dissolução de medicamentos. O método é baseado na reação do fármaco com Cu(II), com posterior complexação de Cu(I) com 4,4'-dicarboxi-2,2'-biquinolina (BQA) e detecção espectrofotométrica. Foi observada resposta linear entre 25 e 300 μmol L -1 captopril, com limite de detecção de 7 μmol L -1 (99,7% de confiança). O coeficiente de variação (n = 20) e a frequência de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Apesar de resultados distintos terem sido obtidos para cada fármaco, a melhor resposta, considerando o sinal analítico e a reprodutibilidade, foi obtida em pH 7,0, no qual o sistema tampão apresenta sua maior capacidade tamponante. Este pH coincide com o empregado em estudos anteriores, [13][14][15][16][17] exceto no caso da determinação de proteínas. 12 O comprimento do reator afeta tanto o tempo de residência, quanto a dispersão da amostra.…”
Section: Otimização Das Variáveisunclassified
“…Apesar de resultados distintos terem sido obtidos para cada fármaco, a melhor resposta, considerando o sinal analítico e a reprodutibilidade, foi obtida em pH 7,0, no qual o sistema tampão apresenta sua maior capacidade tamponante. Este pH coincide com o empregado em estudos anteriores, [13][14][15][16][17] exceto no caso da determinação de proteínas. 12 O comprimento do reator afeta tanto o tempo de residência, quanto a dispersão da amostra.…”
Section: Otimização Das Variáveisunclassified
“…Existing analytical methods to detect uric acid in biofluids include spectroscopy, chromatography, electrochemistry, membrane and capillary electrophoresis (Gochman and Schmitz, 1971 ; Kageyama, 1971 ; Kabasakalian et al, 1973 ; Inoue et al, 2003 ; Perelló et al, 2005 ; Cooper et al, 2006 ; Arora et al, 2009 ; Uricase/PAP test, 2009 ; Bhawna and Pundir, 2010 ; Rocha and Rocha, 2010 ; Amir et al, 2011 ; Sanchez et al, 2011 ; Sidorova and Grigoriev, 2012 ; Hamzah et al, 2013 ; WitkowskaNery et al, 2016 ). Most conventional spectrophotometric methods for uric acid detection involve colorimetric enzymatic reaction, where.…”
Section: Introductionmentioning
confidence: 99%
“…uric acid is oxidized in the presence of uricase and forms allantoin (C4H6N4O3), carbon dioxide and hydrogen peroxide (Gochman and Schmitz, 1971 ; Kageyama, 1971 ; Kabasakalian et al, 1973 ; Uricase/PAP test, 2009 ; Rocha and Rocha, 2010 ; Hamzah et al, 2013 ). In addition, researchers have reported a spectrophotometric method based on the reduction of Cu(II) ions to Cu(I) ions in presence of urinary uric acid (Rocha and Rocha, 2010 ; Sanchez et al, 2011 ). Amir et al have reported a flow injection spectrophotometric method based on the reduction of potassium ferricyanide in presence of uric acid to potassium ferrocyanide (Amir et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Because of its importance for human health, a variety of analytical procedures for its determination have been proposed, employing separation techniques such as high‐performance liquid chromatography (HPLC) and capillary electrophoresis . The following procedures have been employed as detection techniques: voltammetry , spectrophotometry and chemiluminescence .…”
Section: Introductionmentioning
confidence: 99%